Examining Coherence Markers Use on the Abstracts of English Graduate Students’ Final Academic Writing - Ahmad Murodi; Ratna Sari Dewi; Kustiwan Syarief; Sri Rejeki (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research aimed to describe the use of Coherence in the thesis abstracts of the graduate program of the English Education Department of UIN Syarif Hidayatullah Jakarta. The descriptive qualitative analysis was used as the methodological design of this research that attempted to describe the phenomenon of discourse analysis, especially about coherence in the abstracts of the graduate program of the English Education Department of UIN Syarif Hidayatullah Jakarta. Some steps were conducted to collect the data, in which ten chosen abstracts were collected from the repository of UIN Syarif Hidayatullah Jakarta and analyzed to examine the types of Coherence proposed by Kehler (2002), the topical subject and the topical progression to see how they build coherence in the abstracts. This research shows that four out of eleven types of Coherence proposed by Kehler (2002) are used in twenty abstracts, including Parallel, Contrast, Generalization, and Explanation. Meanwhile, the topical subject shows mood as the dominant topical subject with a 91.74% percentage. In Addition, Sequential progression is a dominant Type of Topical Progression. Furthermore, Discourse Topic is hard to analyze because the abstracts only have one paragraph, so the discourse topic is analyzed based on the terms that frequently emerge to interpret the discourse topic. Finally, this study is expected to contribute to the development of language study, especially for Discourse Analysis, and it is also hoped to contribute to the education field, especially for university students, to improve the quality of English writing in abstracts of their research papers.